Design of the Application of Religious Tolerance and Its Relevance to the Psychology of Religion Elementary School, Junior High School , Senior High School and PT - Ratu Bilqis Assyfa (Insight School Academy, 2023)
Indonesia is a country that has a variety of cultures, ethnicities, languages, and religions. To appreciate these differences, it is necessary to have a sense of tolerance. The problems that often occur in Indonesia are related to religious tolerance. Implementing religious tolerance at the level of children is certainly different. This study aims to design the concept of implementing religious tolerance at the elementary, junior high, high school, and university levels. This study uses a qualitative method with a psychological approach involving many references to related articles. Research data sources are research results and existing theories. data collection using documentation with content analysis as the analysis technique. The results of this study are the design of the concept of tolerance at the elementary, junior high, high school, and university levels. This research is recommended for teachers to carry out strategies and understand that religious tolerance is very important to learn. A suggestion for further study is to implement the designs made at each level.